New energy levels of the 4s24p5s, 4s24p4d and 4s24p5p configurations of the Kr v spectrum - Raineri, María Mónica (2002)
The spectrum of four times-ionized krypton (Kr v) has been observed in the 240-2500 Â wavelength range. Three of the four possible levels of the 4s24p5s configuration and two of the three remaining energy level values for the 4s24p4d configurations were determined. Nine of the ten possible levels for the 4s24p5p configuration are also reported. The observed configurations were interpreted theoretically by means of Hartree-Fock relativistic calculations and a least squares fit of the energy parameters to the observed levels. 111 new classified lines are reported among the 4s24p2, 4s24p5p, 4s4p3, 4s24p5s, and 4s24p4d configurations.